The effect of HIV and an Antiretroviral treatment programme on Tuberculosis transmission, incidence and prevalence in a South African Township - Middelkoop, Keren (Department of Medicine, 2015)
This doctoral work aimed to describe the epidemiology of TB in a high HIV and TB prevalent community from 1997 to 2008, and to assess the effect of HIV and a highly active antiretroviral therapy (HAART) programme on the TB epidemic in this setting.